The measurement of active errors: methodological issues. (26th November 2003) - Lilford, R J; Mohammed, M A; Braunholtz, D; Hofer, T P
Abstract : The value of research in any topic area turns on its validity. Patient safety research has revealed—or, at least, given renewed urgency to—a raft of methodological issues. The meaning and thus the value of empirical research in this field is contingent on getting the methodology right. The need for good methods for the measurement of error is necessary whenever an inference is intended and, since inferences lie at the heart of research and management, there is a huge need to understand better how to make measurements that are meaningful, precise, and accurate. In this paper we consider issues relating to the measurement of error and the need for more research.